Sistem Informasi Bujang Gadis Kota Pagar Alam Berbasis Web - Rahmadi, Lendy; Aprianita, Yossy (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2019)
Each district and the cities in Indonesia have a separate icon to showcase their respective regions. Start from the culture until the potential of tourism object. One of the most well known icon until the territory was visited by many tourists is tourism object. This is shown by the number of domestic tourists and also foreign tourists who visited in each area in Indonesia one of the Pagar Alam town. Pagar Alam town rich natural tourism potential and other tourism.Bujang Gadis PagarAlam town stand since 2002. But submitting information about Bujang Gadis Pagar Alam town it was still not optimat because it still used brochures and word of mount as well as in is’s registration participant had to collect and submit documen directly to the tourism office of Pagar Alam. Of these problem, a Bujang Gadis Pagar Alam town information system is designed. This study uses software Macromedia Dreamwaver, Xampp, PHPprogramming languageandMySQL asdatabase.